Effect of formability parameters on tailor welded blanks AA6061 and AA8011 Sheets. (2022) - Naveen Kumar, M.; Sundeep Kumar, B.; Vasanth Naik, R.; Anitha Lakshmi, A.
Abstract: Aluminum is a lightweight non-ferrous metal which is soft, and its strength is increased by making aluminum alloys. The availability of aluminum in earth's crust is also very abundant, hence aluminum is used in many industrial and defense, automobile, aerospace, marine industries applications. In this study two grades of aluminum alloys are used i.e., AA6061 and AA8011. These alloy sheets are tailor welded using FSW at optimum process parameters of 1120RPM tool speed, 50 mm/min traverse speed, and tilt angle of 2°, with an offset of 1 mm towards advancing side of the tool. The welding is performed at different weld orientations of R0, R30, R60, R90 . Uniaxial tensile testing is performed on hot Forming Machine at different temperatures and strain rates on a total of 16 specimens. Material properties for the welded specimens are determined from the output of tensile testing. Effect of strain rates and temperatures on the material properties are also analyzed.